2016
DOI: 10.4067/s0718-34292016000300004
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of salt and boron-affected soil by addition of organic matter: an investigation into improving tomato plant productivity

Abstract: To mitigate the effect of salt stress and excess B in soil and consequently increase crop yield and improve the behaviour of cv. "Poncho Negro" there are low-cost strategies such as the application of organic amendments. This study aimed at remediating excess salt (150 mM NaCl) and B (20 mg L -1 B) in soil using organic matter treatment (4% and 6%). Stress was supplied by irrigation. The rate of net CO 2 assimilation, B, Na + , K and Ca 2+ content, soluble sugars and proline were measured. All growth parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The relationships between boron and other elements, such as Ca, S, Zn, Si, and Al were used for developing amendments that are intended either for soil improvements or for the alleviation of the toxic effects on plants [174][175][176]. Organic matter, as well as various plant growth modulators, was applied in attempts to mitigate excess boron [177,178]. Developing and applying cost-effective methods for boron removal from irrigation water would solve the problem of the most common anthropogenic source of contamination [124,[179][180][181].…”
Section: Alleviation Of the Effects Of Boron Deficiency And Toxicitymentioning
confidence: 99%
“…The relationships between boron and other elements, such as Ca, S, Zn, Si, and Al were used for developing amendments that are intended either for soil improvements or for the alleviation of the toxic effects on plants [174][175][176]. Organic matter, as well as various plant growth modulators, was applied in attempts to mitigate excess boron [177,178]. Developing and applying cost-effective methods for boron removal from irrigation water would solve the problem of the most common anthropogenic source of contamination [124,[179][180][181].…”
Section: Alleviation Of the Effects Of Boron Deficiency And Toxicitymentioning
confidence: 99%
“…The application of organic amendments in SAS is considered a useful and effective way to increase soil fertility and enhance crop growth [31,157]. The application of organic amendments in SAS increased the biomass yield of alfalfa, Medicago sativa [182]; barley, Hordeum vulgare [31]; cotton, Gossypium hirsutum [143]; maize, Zea mays [32,159,183]; onion, Allium cepa [142]; rice, Oryza sativa [31,153,184]; seepweed, Suaeda salsa [185]; sweet fennel, Foeniculum vulgare [186]; tomato, Solanum lycopersicum [187]; and wheat, Triticum aestivum [139]. The quantitative and qualitative improvements in the growth and yield attributes of crops as affected by abiotic stresses in the presence of different additives might be due to the enhanced photosynthesis, cholorophyll contents, stomatal conductance, water-use efficiency, and synthesis of metabolites [137,[188][189][190][191].…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…Organic manure incorporation into the SAS also increased the N, P, and K contents in rice, Oryza sativa, barley, Hordeum vulgare [31], and sweet fennel, Foeniculum vulgare [186]; K content in rice, Oryza sativa [184,192]; and K and Ca contents in tomato, Solanum lycopersicum [187], while it decreased the Na uptake [31,184,186,187]. Improved soil physical conditions, availability of macro-and micronutrients, and enhanced microbial activities in soil resulting from the incorporation of organic amendments lead to better growth and yield of crops under salt stress [30,175].…”
Section: Effects Of Organic Amendments On the Physical Chemical Andmentioning
confidence: 99%
“…Based on published information about the combined effects of salinity and B concentration [72,73], the current study used relatively higher salinity and B levels in order to test extreme conditions. Some early investigators reported that shoot dry weight responded independently to boron and salinity with no interactive effect [74,75]. Membrane permeability was reported to be the main cause of the difference in B concentration of the crops [56,76].…”
Section: Discussionmentioning
confidence: 99%